PARTISIPASI MASYARAKAT SEKITAR HUTAN DALAM MELESTARIKAN HUTAN ADAT SEBAGAI DAERAH PENYANGGA SUMBER AIR DI DESA MENYABO KECAMATAN TAYAN HULU KABUPATEN SANGGAU - nardi, Milu; rizal, Fah; kandar, Is (Universitas Tanjungpura, 2014)
Indigenous forests have a very large role in the lives of local people of Menyabo and communities around indigenous forest, the forest conservation effort in order to be able to benefits for future. In utilizing forest communities have the local wisdom in managing forests with its rules or norms that have been applied over the years and is complied with and adhered to by community members, the norms are so called customary norms. The method that used in this research is descriptive whereas for data collection used structured interviews using questionnaires. The number of respondents in this research study are 81 respondents. The research results revealed that the communities participation of forest in conserving indigenous forests as a buffer zone water resources tends to be high ie there are 62 respondents (76.55%) who have high participation, there were 8 respondents (9.87%) which had medium participation, and 11 respondents (13.58%) who had low participation. Â Keyword : participation, community, Indigenous forest, Source of Water.